Studies on alumina dispersion-strengthened copper composites through ball milling and mechanical alloying method - Hussain, Zuhailawati; Koay, Han Keong (Penerbit UTM Press, 2005)
Oxide dispersion-strengthened copper has the ability to retain most of its properties at elevated temperatures. Among various processes, powder metallurgy route is ideal because of its efficiency in dispersing fine oxide particles. In this study, copper-alumina composites is produced through powder metallurgy route whereby copper powder, which is the matrix, was mixed with alumina powder, which act as reinforcement. Powder mixtures with different compositions of alumina (2.5wt%, 5wt%, 7.5wt% and 10wt%) were prepared. The mixtures were then mixed either by (a) blending process for 45 minutes in a ball mill or (b) mechanical alloying for 45 minutes in a planetary mill. The mixture was then compacted at 200 MPa and sintered under argon atmosphere at 950°C for 1 hour. Results showed that mechanical alloying has produced Cu-Al2O3 composite with better hardness and lower electrical conductivity compared to those prepared by ball milling method